2017
DOI: 10.1103/physreva.95.032115
|View full text |Cite
|
Sign up to set email alerts
|

Numerical approach to simulating interference phenomena in a cavity with two oscillating mirrors

Abstract: We study photon creation in a cavity with two perfectly conducting moving mirrors. We derive the dynamic equations of the modes and study different situations concerning various movements of the walls, such as translational or breathing modes. We can even apply our approach to one or three dimensional cavities and reobtain well known results of cavities with one moving mirror. We compare the numerical results with analytical predictions and discuss the effects of the intermode coupling in detail as well as the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
2
8
0
Order By: Relevance
“…2, corresponding to the case with L 0 = 1 (ω 0 = 2π), one can see an agreement between N app (circles) and N exa (crosses). In addition, both results are in agreement with numerical ones found by Ruser 29 (other numerical approaches to solve DCE problems have also been developed [30][31][32][33][34] ). We also verified agreement between N exa [Eq.…”
Section: Comparison With Approximate Analytical Resultssupporting
confidence: 88%
“…2, corresponding to the case with L 0 = 1 (ω 0 = 2π), one can see an agreement between N app (circles) and N exa (crosses). In addition, both results are in agreement with numerical ones found by Ruser 29 (other numerical approaches to solve DCE problems have also been developed [30][31][32][33][34] ). We also verified agreement between N exa [Eq.…”
Section: Comparison With Approximate Analytical Resultssupporting
confidence: 88%
“…For other approaches to solving equations like (28), see, e.g., [99,125,126]. Recently, these equations were solved numerically in the 1D and 3D cases, for one and two moving boundaries, in the study [127].…”
Section: Expansions Over the Instantaneous Basismentioning
confidence: 99%
“…L 0 is a function of time, that we will denote t) . In this scenario, one may impose Dirichlet boundary conditions at both ends of the cavity, say Φ(0, t) = Φ(L(t), t) = 0 [20][21][22]. In fact, it has been demonstrated that non stationary boundary conditions effects in a cavity can be implemented in a circuit QED system [23,24].…”
Section: The Systemmentioning
confidence: 99%